Caracterizacion mediante el uso de RAPD de la poblacion de Pinus Radiata del pais vasco (España) - Aragones, A.=700 1 Espinel, S.; Ritter, E.
(En, Es)
ilus., 17 ref.
Keywords: PINUS RADIATA; PROCEDENCIA; PCR; ESPAÑA; RAPD